KARAKTERISTIK ANALOGI SISWA SEKOLAH DASAR DALAM PENGAJUAN MASALAH LUAS DAERAH - Eksanti, Aulia Risa; Amir, Mohammad Faizal (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This study aims to identify the characteristics of elementary school students' analogies in proposing area problems. The method used in this research is descriptive qualitative using a case study approach. The characteristics of analogy in the submission of area problems can be categorized into three: (1) Identical-reformulation is rearranging the elements in the problem structure in ways that do not change the nature of the problem. (2) Identical-different-reconstruction is modifying and maintaining some elements of the form in the initial problem so that the resulting problem looks slightly different. (3) Different-imitation is changing and adding new shape elements that are not in the initial problem to produce a different problem. The results of the research showed that the characteristic most often found in students is imitation, where the problem produced is different from the initial problem given. So the different imitation characteristics that appear most often correspond to replacement characteristics, namely the problem posing product based on the initial problem or source problem by changing the context of the problem, namely changing the shape of the cake slice.